Her holiday secret [large type] - Navarro, Jolene (Navarro, Jolene. Cowboys of Diamondback Ranch, 2021)
"Six years ago, pregnant teenager Catalina Wimberly left town without a word to protect her childhood sweetheart Andres Sanchez's future. Now she's back for the holidays and ready to reveal her secret - she and Andres have a little girl. But as they begin to feel a lot like family, will Catalina turn down her dream job and stay beyond Christmas?" -- Back cover.